WAQF INVESTMENT: A CASE STUDY OF DOMPET DHUAFA REPUBLIKA, INDONESIA - Candra, Hari; Ab Rahman, Asmak (Jurnal Syariah, 2010)
This paper discusses the method of waqf investment by Dompet Dhuafa Republika, Indonesia. The study analyzes the information gained from the interview sessions and the reports issued relating to the investment methods applied by Dompet Dhuafa Republika, Indonesia. The study revealed that waqf investment in Dompet Dhuafa Republika focuses on the development of the waqf assets used in helping the development of the socio-economy of the community. At Dompet Dhuafa Republika, the waqf assets are invested in the banking institution, Baitul Mal wat Tamwil (BMT) and capital for the needy who are involved in Small and Medium Enterprises based on mudarabah and musyarakah contracts.